Simulation Method in Social Studies Learning: Student Learning Outcomes at Elementary School - Alestina Rommer; Fransheine Rumtutuly; Jekriel Septory (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This research addresses the low social studies learning outcomes among fifth-grade students at Elementary School, primarily caused by conventional teaching methods that foster student passivity and difficulty in grasping abstract historical concepts. The study aims to improve learning outcomes by implementing the simulation method, specifically focusing on the history of Indonesian independence. Utilizing a Classroom Action Research (CAR) design across two cycles, the study involved 22 students (13 females and 9 males) at Elementary School Wakarleli. Data were collected through observation, achievement tests, and documentation, then analyzed using quantitative descriptive techniques and classical mastery benchmarks. The findings revealed significant improvements at every stage: in the pre-action phase, only 6 students (27.27%) achieved mastery with an average score of 54.44. Following the implementation of simulations in Cycle I, mastery rose to 17 students (77.27%), and reached 19 students (86.36%) in Cycle II after reflective refinements. The simulation method successfully transformed abstract history into concrete, contextual experiences, creating an active and enjoyable learning environment. Practically, this study recommends simulations as an effective strategy for elementary teachers to boost student motivation and contextual understanding. Academically, these results provide a foundation for further research into the effectiveness of simulation methods across broader social studies curricula or different grade levels.